Design and Initial Performance Characterization of DC Electric Motor as a Propulsion System for Small-Scale Fishing Vessels - Rahmat Rabbani; Fis Purwangka; Budhi Hascaryo Iskandar; Dwi Putra Yuwandana (International Journal of Marine Engineering Innovation and Research, 2026)
The majority of fishermen in Indonesia, approximately 95.6% are small-scale fishermen who operate daily using small vessels powered by outboard engines. This reliance on fossil fuels and the environmental impact, including air and noise pollution, highlights the need for more sustainable alternatives such as electric motors. This study aims to design an electric propulsion system for small fishing vessels by adapting electric motors commonly used in electric scooters and evaluating their initial performance. The performance test was conducted to assess the system's feasibility and to estimate energy requirements and optimal battery capacity. The results indicate that electric motors can be utilized as a propulsion system with essential components including a dynamo, battery, controller, shaft, and propeller, reaching Technology Readiness Level (TRL) 2. The initial performance is not yet optimal and requires further refinement of components. The estimated energy requirement is 282.24 Wh, with a recommended battery specification of 24 V 12 Ah for further testing.